Civilians and warfare in world history - Foote, Nicola; Williams, Nadya (Cass military studies, 2018)
This book explores the role played by civilians in shaping the outcomes of military combat across time and place. By highlighting civilian military agency and broadening the sense of which actors affect strategic outcomes, the book also contributes to a richer understanding of war itself. This book will be of much interest to students of military studies, international history, international relations and war and conflict studies.